Hard-core boson approach to S=1 magnets near saturation magnetic field - Wang, Han-Ting (Physica. B, Condensed matter, 2024)
A hard-core boson representation for an S=1 spin is developed and applied to the study of S=1 Heisenberg models with Ising and single-ion anisotropies near saturation magnetic field. By solving secular equation, energy spectra and existence region of two-magnon bound states, saturation magnetic field and a tricritical point to separate Bose–Einstein condensation (BEC) of one-magnon excitations and of two-magnon bound states are obtained. In combination with many-body techniques, effective interactions between two bosons are calculated in low density limit and BEC-induced long-range spin order and ferronematic order are discussed. A hard-core boson representation for a spin with a general spin amplitude S is also presented and compared with the Holstein–Primakoff transformation. The interconversion between one-magnon and two-magnon excitations makes it possible to mimick cold atom-molecule systems with S=1 magnets, and vice versa. •Hard-core boson representation for S=1 spin.•Tricritical point to separate BEC of one-magnon excitations and of two-magnon bound states.•Hard-core boson representation for a spin with general spin amplitude S.